344 Detection of ERG Rearrangement in Formalin-Fixed Paraffin-Embedded Tissue of Prostatic Adenocarcinoma by Targeted RNA-seq. (11th January 2018) - Saeed, Faisal; Zhuge, Jian; Huang, Weihua; Yang, Ximing; Volyanskyy, Konstantin; Dimitrova, Nevenka; Fallon, John; Zhong, Minghao
Abstract: Introduction: Chromosomal translocations involving the erythroblast transformation-specific (ETS) transcription factors, such as ERG and ETV1, are frequent events in human prostate cancer pathogenesis. In particular, the TMPRSS2-ERG fusion gene has recently been found to be the most frequent gene rearrangement in prostate cancers. Previously, IHC stain and FISH assay have been used to detect ERG translocation. However, these methods do not provide detailed information, such as the exact breakpoint and partner gene. Here, we want to test the feasibility of detection of ERG translocation by targeted RNA-seq. Methods and Materials: Tissue microarray (TMA) was constructed from 27 cases of prostatic adenocarcinoma. TMA slides were subjected to ERG immunostaining. Cases with positive ERG staining were identified. For targeted RNA-seq, we used Archer FusionPlex (ArcherDX, Boulder, CO) Solid Tumor Kit, which uses Anchored Multiplex PCR-based enrichment method and can detect fusions associated with >50 genes. Both ERG-positive and -negative tissue was subject for this assay. Results: Eight samples (four of ERG+ prostate cancer and four of ERG– tissue) generated a total of two GB sequencing data. ERG translocation was not found in any of the four samples of ERG– tissue. TMPRSS2-ERG fusion was identified in one of the samples of ERG+ prostate cancer. Conclusions: Our preliminary test demonstrated that it is feasible to detect ERG rearrangement in formalin-fixed paraffin-embedded tissue by targeted RNA-seq, which could provide much more detailed information than other traditional methods. However, this test is still very challenging and requires strong bioinformatics support.